The Impact of Social Network Sites on Knowledge and Information Sharing to Students in the Open Distance Learning Scheme - Ajiboye Adeleke R; Bakare Maroofat; Usman-Hamza Fatima; Sulyman Shakirat (International Journal of Applied Business and Information Systems, 2018)
This study examines the impact of selected Social Network Platforms on the dissemination of knowledge and information for students of the National Open University of Nigeria. Three major social network platforms are considered in this study, they are: Facebook, Web-blogs and YouTube. Research questions were asked based on the objectives of this study and a number of hypotheses were formulated. The questionnaire used as the survey instrument was carefully designed and distributed to some students within the study domain. This comprised of the registered students for 2016/2017 Academic Session at the National Open University of Nigeria, Ilorin and Oshogbo Study Centres. Questionnaires were administered to a total of 600 students in the two centres. The data collected are analyzed using Statistical Package for Social Sciences (SPSS). Findings from this study show that, 80% of the respondents indicate the positive impact of the three social network platforms under study. The impacts of the three networks are also found to be significant. The study further reveals that, effective utilization of educational features of Social Network Platforms has a great and tremendous advantage to students if optimally put to use. It is recommended that students who find the use of Social Network Platforms distracting to academics, should reduce the time they dedicate to exploration of online resources and in particular on these platforms: Facebook, Web-blogs and YouTube.